Cyclic performance of bolted end-plate RWS connection with vertical-slits. (October 2020) - Nazaralizadeh, Hamidreza; Ronagh, Hamid; Memarzadeh, Parham; Behnamfar, Farhad
Abstract: The reduced beam section (RBS) connections are widely used in construction buildings due to their desirable ductility and strength. The current reduced web section (RWS) connections are produced by a reduction in the beam web as circular or rectangular cuts or as horizontal slits. This article has proposed a new detail for the RWS bolted connection by creating vertical-slits in the beam web. The aim of this investigation is the evaluation of its cyclic performance in comparison with the conventional RBS connection. Two specimens, one with vertical-slits in the web (VS-RWS) and the other one with a radial-cut in the flange (RC-RBS), were experimentally tested and the results were compared. Moreover, numerical models were employed to evaluate the behavior of connections in detail. These two connections were able to move the plastic hinge region away from the column face, exhibit good hysteresis behavior, and satisfy the AISC requirements for special moment-resisting frames. The results also showed that the flexural capacity of the proposed VS-RWS connection is 10% higher than that of the conventional RC-RBS one, while their ductility and energy dissipation were almost the same. An important advantage of VS-RWS over RC-RBS is its ability to prevent the lateral-torsional instability. Besides, a numerical study was conducted to investigate the performances of various cut shapes RWS connections with certain overall dimensions and location of the cutting region in terms of hysteresis curves, rupture index and end-plate deformations. Graphical abstract: Image 1 Highlights: A novel RWS connection with vertical-slits (VS-RWS) was proposed and examined. Full-scale experimental and numerical tests carried out on VS-RWS and common RBS. VS-RWS had a good performance, in terms of stress reduction over the welding lines. Vertical slits were sufficient to remove the plastic hinge away from the column face. Based on conducted parametric study, the cutting depth is an important parameter.